2020
DOI: 10.3389/fcell.2020.00770
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A7 Regulates Endometrial Receptivity

Abstract: A limited window of receptivity is a prerequisite of reproductive success. Indispensable receptivity genes include cyclooxygenase 2 (COX2), an enzyme accomplishing formation of prostaglandin E 2 (PGE 2). A powerful regulator of PGE 2 formation is Annexin A7 (ANXA7). The present study thus explored whether ANXA7 impacts on implantation and fertility. Here we show that ANXA7 is expressed in endometrial tissue and increases upon decidual transformation of human endometrial stromal cells (HESCs) in a timedependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Upon manual interrogation, we also noted that several of the significantly upregulated proteins in Tsc‐sEV‐treated cells have previously been shown to be involved in implantation (BSG [125], CD44 [126,127], TAGLN2 [95], ANXA2 [128], PFN1) [129], trophoblast invasion (CSTD [130], THBS1 [131], CDCP1 [132], LGALS3) [133], and endometrial receptivity (CLIC4 [134], EGFR) [135]. Amongst the proteins found in higher abundance, 6 proteins (DPP4, ASS1, ANXA4, COTL1, MRPS2, SOD2) are also associated with endometrial receptivity [136].…”
Section: Resultsmentioning
confidence: 99%
“…Upon manual interrogation, we also noted that several of the significantly upregulated proteins in Tsc‐sEV‐treated cells have previously been shown to be involved in implantation (BSG [125], CD44 [126,127], TAGLN2 [95], ANXA2 [128], PFN1) [129], trophoblast invasion (CSTD [130], THBS1 [131], CDCP1 [132], LGALS3) [133], and endometrial receptivity (CLIC4 [134], EGFR) [135]. Amongst the proteins found in higher abundance, 6 proteins (DPP4, ASS1, ANXA4, COTL1, MRPS2, SOD2) are also associated with endometrial receptivity [136].…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced PGE 2 formation upon AnxA7 depletion appears relevant also for implantation and fertility [ 380 ]. In women suffering from recurrent pregnancy loss, decreased AnxA7 levels in endometrial biopsies during the midluteal window of implantation were observed.…”
Section: Anxa7mentioning
confidence: 99%
“…In women suffering from recurrent pregnancy loss, decreased AnxA7 levels in endometrial biopsies during the midluteal window of implantation were observed. This correlated with the viable Anxa7 −/− strain showing significantly increased implantation sites and litter sizes, indicating that ANXA7-mediated regulation of COX-dependent PGE 2 production contributes to regulating endometrial receptivity and implantation [ 380 ].…”
Section: Anxa7mentioning
confidence: 99%
“…Embryonic implantation is the crucial biological process in the reproduction of mammals, which allows the activated blastocysts to connect with endometrium by ways of localization, adhesion and invasion. Endometrial receptivity is a parameter to describe embryo implantation onto the endometrium, on which a successful pregnancy is depended [ 1–4 ]. Previous studies have shown that administration of ovulation-inducing drugs in the controlled ovarian hyperstimulation (COH) might bring about an interference of endogenous steroids to endometrium physiological regulation, thus affecting the endometrium receptivity within implantation window period, leading to lower rates in clinical pregnancy and higher ones in abortion.…”
Section: Introductionmentioning
confidence: 99%